To Bully or Not to Bully: Understanding the Role of Uncertainty in Trademark Enforcement Decisions - Kiser, Jessica M. (The Columbia Journal of Law & the Arts, 2014)
Companies like Starbucks and Chick-fil-A are routinely labeled trademark bullies. The term “trademark bully” is typically used to describe a large company that uses aggressive intimidation tactics and threats of prolonged trademark infringement litigation to stop small businesses and individuals from using their own trademarks where the stated claims of infringement are likely spurious or non-existent. Trademark bullying harms competition and chills the free speech interests of those seeking to use trademarks for criticism and parody as permitted by the fair use doctrine. This Article identifies two fundamental causes that interact to encourage the aggressive tactics used by trademark bullies. First, trademark law imposes a vague duty on trademark owners to “police” third party trademark use for potential infringement. This uncertain duty renders trademark owners unable to accurately predict the risk of harm that third parties pose to their trademarks. Secondly, inherent cognitive biases affecting evaluations of such risk lead to systematic judgment errors and overestimation of the risk involved, thereby encouraging aggressive trademark enforcement. This Article uses prospect theory, an empirical social science approach to understanding human decision making, to characterize the psychological phenomena, including loss aversion and overestimation of risk, that motivate trademark bullies. Prospect theory explains apparently irrational decision making by trademark bullies. Recently proposed solutions for trademark bullying mistakenly assume that the trademark bully conducts a rational cost-benefit analysis prior to acting. Better solutions require an understanding of the actual psychological processes that underlie these aggressive tactics.